The Gram stain: Implication in blood culture reporting. (April 2023) - KP, Angitha; Mohapatra, Sarita; Gautam, Hitender; Nityadarshini, Neha; Das, Bharat Chandra; Yadav, Viswanath Kumar
Bloodstream infections are life-threatening. They are responsible for prolonged hospital stays and high healthcare costs. Clinical microbiology has an essential role to play in its management. Direct Gram-stain reporting from positive blood culture bottles has been found helpful. We aimed to evaluate the use of the automated blood culture system in adjunct to the conventional Gram-stain technique, with a direct antimicrobial susceptibility test on the second day. Concordance was highly satisfactory.